2011
DOI: 10.1007/978-94-007-2488-4_27
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Carbon Compounds: N-doped Fullerene (C50N10)O3H10 and “Pyridine” Nanocarbon

Abstract: Fullerene N-doped fullerene (C 50 N 10 )O 3 H 10 has been synthesized at thermal transformation of pyridine molecules. The synthesis was carried out at special reaction conditions, which are optimum for polycondensation of pyridine molecules. O and H atoms bind to nitrogen atoms and they are positioned exohedrally with respect to the pyridine net, (C 50 N 10 ). Nitrogen atoms in (C 50 N 10 )O 3 H 10 molecule reside in a hypercoordinated state: there are four bonds with carbon atoms belonging to the pyridine ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Earlier [25][26][27][28] we have been systematically studied the influence of various technological parameters on composition of obtained products and, in particular, condensed substances formed at heat treatment of hydrocarbons. On the basis of the experimental results the new method of pyrolysis (NMP) of organic vapours was developed [28][29][30][31]. This method differs from two already known processes of pyrolysis [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier [25][26][27][28] we have been systematically studied the influence of various technological parameters on composition of obtained products and, in particular, condensed substances formed at heat treatment of hydrocarbons. On the basis of the experimental results the new method of pyrolysis (NMP) of organic vapours was developed [28][29][30][31]. This method differs from two already known processes of pyrolysis [32].…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine (C 5 NH 5 ) is heterocyclic analogue of benzene (С 6 Н 6 ) therefore from precursors C 5 N or С 3 -С 5 should be formed accordingly heteroatomic or monoatomic fullerenes and quasi-fullerenes. Our preliminary researches [29,30] have shown that at pyridine pyrolysis large nitrogen-carbon containing molecules are formed which further study represents not only scientific but also practical interest.…”
Section: Products 1b Of Zone Bmentioning
confidence: 94%
“…Fullerenes received attention from the researchers all over the word and led to the synthesis of new compounds [1][2][3][4] and identification of different applications due to their hardness, high electron affinity, increased incident light intensity, and biological activities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%